Thermal Effect of Wind Generation on Conventional Generator in a Microgrid - Azmi Hashim; Kwok L Lo (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In order to reduce CO2 emissions, which is one of the key strategy in combatting global warming, development of wind energy technology as source of renewable energy has become more important globally. However, the variability of the wind speeds leads to the intermittent nature of wind power generation. The conventional generators in the system must be able to compensate this fluctuation to maintain system stability and meet the load demand in the grid. This in turn may increase the temperature of the conventional generators beyond what normally occurs without wind generation in the grid. The aim of the paper is to inestigate the effect of thermal heating of the generators due to the variable output of wind generation in different time of the year in a microgrid by proposing proper modelling in the simulation. The simulations are done in 24 hours period in four different time of the years corresponding to different seasons of the year.